Effect of Multi-Sensory Stimulation of Neonates on Stress Level of Mothers with Premature Neonate Hospitalized in Neonatal Intensive Care Unit - Razieh Derakhshani; Naiire Salmani; Hossien Tavangar (Hamadan University of Medical Sciences, 2022)
Background and Objective: Premature birth is an unexpected event that causes a lot of stress for parents as they are not psychologically and emotionally prepared to face it. Therefore, this study aimed to determine the effect of multi-sensory stimulation of neonates by mothers on the stress level of mothers with premature neonates hospitalized in the Neonatal Intensive Care Unit (NICU). Materials and Methods: This quasi-experimental study was performed on 80 mothers (in experimental and control groups) who were selected using the census method in the NICU of Shahid Sadoughi Hospital, in Yazd, Iran. The infants in the experimental group were stimulated twice a day from the third to the sixth day. Data were collected using demographic characteristics form and Parental Stress Scale that were completed before and after the intervention. Data were analyzed in SPSS software (version 20) through statistical tests. Results: There was no significant difference between the mean stress levels in the two study groups before intervention; however, there were significant differences in intervention and control groups post-intervention in the mean±SD score of stress (P<0.001) in areas of scenes and sounds (2.26±0.40 and 2.63±0.47), infant's appearance and behavior (3.79±0.29 and 4.05±0.25), relationship with the infant and parental role (2.60±0.38 and 3.41±0.33), and overall stress level (4.08±0.64 and 4.88±0.31). No significant difference was observed between the mean stress level in the area of communication and personnel's behavior (P<0.3). Conclusion: The use of multi-sensory stimulation had a significant effect on reducing the stress in mothers with premature infants admitted to NICU. Therefore, this method is recommended to be used to improve the mental status of mothers.